2007
DOI: 10.2460/ajvr.68.5.483
|View full text |Cite
|
Sign up to set email alerts
|

Response of hypotensive dogs to dopamine hydrochloride and dobutamine hydrochloride during deep isoflurane anesthesia

Abstract: In isoflurane-anesthetized dogs, a guideline dose for dopamine of 7 microg/kg/min is suggested; dobutamine alone did not improve MAP. Data regarding cardiovascular and UrO effects indicated that the combination of dopamine and dobutamine did not provide greater benefit than use of dopamine alone in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Previous studies in horses report comparable changes in systemic cardiovascular parameters . Studies on dogs using similar doses found significant increases in CO and SV , while a dose of 14 μg/kg bwt/min led to a marked increase in SVR . We did not use higher doses due to the risk of severe cardiac arrhythmias in horses reported with doses up to 10 μg/kg bwt/min .…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies in horses report comparable changes in systemic cardiovascular parameters . Studies on dogs using similar doses found significant increases in CO and SV , while a dose of 14 μg/kg bwt/min led to a marked increase in SVR . We did not use higher doses due to the risk of severe cardiac arrhythmias in horses reported with doses up to 10 μg/kg bwt/min .…”
Section: Discussionmentioning
confidence: 70%
“…Arguably, the variable etiologies of hypotension limit the utility of such guidelines, despite literature relating to management strategies for hypotension (Rosati et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine has been reported to increase renal blood flow at dosages of less than 5 mcg/kg/min (and to decrease it to baseline at 10 mcg/kg/min) and may increase urine output, 1-3 but dopamine therapy does not appear to provide any low-dose renal-protective efficacy in people. 4,5 When administered to critically ill people, 6 septic dogs 7 (in the author's experience), anesthetized dogs, [8][9][10] and anesthetized cats, 11 dopamine generally causes a modest vasoconstriction and increase in blood pressure with little change or modest increases in cardiac output. In one study of anesthetized cats, 12 dopamine was associated with vasodilation and increases in heart rate, cardiac output, and blood pressure.…”
Section: Hypotensionmentioning
confidence: 99%
“…When dobutamine is given to critically ill humans, 6,13 septic dogs 7 (in the author's experience), anesthetized dogs, [8][9][10]14 anesthetized cats, 12,15 and anesthetized foals, 16,17 it generally causes modest vasodilation and a marked increase in cardiac output with little change in blood pressure.…”
Section: Dobutaminementioning
confidence: 99%
See 1 more Smart Citation